Uso da linguagem documentária na busca da informação em bibliotecas universitárias: a perspectiva dos deficientes visuais - Vitorini, Érica Fernanda [UNESP] (2015)
Documentary languages, as instruments for representation and measurement of information access must include all users, without distinction. Thus, a study about the use of documentary language applied to information retrieval, was taken, considering the visually impaired perspective, aiming to gather information about the real needs and difficulties these users face trying to access information. The study was taken in public universities in the state of São Paulo which offer accessibility laboratories for visually impaired users. Hence, the study was carried with five visually impaired users and five librarians from: Cesar Lattes Central Library (BCCL) Accessibility Laboratory (LAB) at University of Campinas (Unicamp); Science and Literature Library Accessibility and Development Laboratory (LAD) at Universidade Estadual Paulista (Unesp) and Special Groups of Users Attendance Program: Visually Impaired (PROVER) at Federal University of São Carlos (UFSCar). The methodology used was focus group. From collected data, two analysis categories were established, based on the declarations emitted by the users, in comparison to Information Science literature. Results show some significant advances were already reached in accessibility laboratories, although some investment in research is still required, when it concerns to developing and using a library catalog, and especially referring to documentary language. The need for formalization and standardization of criteria for the offer of products and services designed for visually impaired users was also observed.